Melatonin pretreatment improves gastric mucosal blood flow and maintains intestinal barrier function during hemorrhagic shock in dogs. (May 2017) - Vollmer, Christian; Weber, Andreas P. M.; Wallenfang, Martin; Hoffmann, Till; Mettler‐Altmann, Tabea; Truse, Richard; Bauer, Inge; Picker, Olaf; Mathes, Alexander M.
ABSTRACT: Objective: Melatonin improves hepatic perfusion after hemorrhagic shock and may reduce stress‐induced gastric lesions. This study was designed to investigate whether pretreatment with melatonin may influence gastric mucosal microcirculatory perfusion (μflow), oxygenation (μHbO2 ), or intestinal barrier function during physiological and hemorrhagic conditions in dogs. Methods: In a randomized crossover study, five anesthetized foxhounds received melatonin 100 μg kg −1 or vehicle (ethanol 5%) intravenously in the absence or presence of hemorrhagic shock (60 minutes, −20% blood volume). Systemic hemodynamic variables, gastric mucosal perfusion, and oxygenation were recorded continuously; intestinal barrier function was assessed intermittently via xylose absorption. Results: During hemorrhagic shock, melatonin significantly attenuated the decrease in μflow, compared with vehicle (−19±9 vs −43±10 aU, P <.05), without influence on μHbO2 . A significant increase in xylose absorption was detected during hemorrhage in vehicle‐treated dogs, compared with sham‐operated animals (13±2 vs 8±1 relative amounts, P <.05); this was absent in melatonin‐treated animals (6±1 relative amounts). Melatonin did not influence macrocirculation. Conclusions: Melatonin improves regional blood flow suggesting improved oxygen delivery in gastric mucosa during hemorrhagic shock. This could provide a mechanism for the observed protection of intestinal barrier function in dogs.